PANDANGAN NU-MUHAMMADIYYAH TENTANG HADITS IFTIRÃ‚Q AL-UMMAH - Hasan Suâ€™aidi (IAIN Pekalongan, 2010)
The declaring of the Hadist â€œMuslims will be divided into 73 groups; all of them will go to hell, but only the one that will be saved, and it is called Ahlu al-Sunnah wa al-Jamaâ€™ahâ€, well-known as Hadist of IftirÃ¢q al-Ummah, made some multi-interpretations among Muslims, including distortion ones. The hadist was considered to be unsuitable for plural society. Muslims traditionally leaned to claim their own group as â€œthe saved oneâ€ (Ahlu al-Sunnah wa al-Jamaâ€™ah) and disrespect to others. This kind of interpretation will likely be unfair to develop multi cultural and plural country like Indonesia. This research exposes the real meaning of the Hadist according to the Islamic law maker (Allah as God and Muhammad as his prophet) through the depth research of Hadist. This action aims to find out the appropriate meaning of the Hadist instead of bias one. In another side, this research shows up the meaning of the Hadist according to Islamic mass organizations, as representation of Muslim groups. This research used descriptive analytic method, which combined field research with library research mutually, so were the primary and secondary data.